2021
DOI: 10.3390/ijms22052592
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Human ABCB1 and ABCG2 Reduces the Susceptibility of Cancer Cells to the Histone Deacetylase 6-Specific Inhibitor Citarinostat

Abstract: Citarinostat (ACY-241) is a promising oral histone deacetylase 6 (HDAC6)-selective inhibitor currently in clinical trials for the treatment of multiple myeloma (MM) and non-small-cell lung cancer (NSCLC). However, the inevitable emergence of resistance to citarinostat may reduce its clinical effectiveness in cancer patients and limit its clinical usefulness in the future. In this study, we investigated the potential role of the multidrug efflux transporters ABCB1 and ABCG2, which are two of the most common mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 73 publications
0
10
0
Order By: Relevance
“…ABCB1 (also known as MDR1/multidrug‐resistance 1, P‐gp/P‐glycoprotein) is a plasma membrane protein and first discovered in multidrug‐resistant tumor cells. ABCB1 can extrude a large number of medically relevant compounds from cells and causes drug resistance 50–52 . In this study, we found that the expression of P‐gp is regulated by GEM or DDP or both, and also found that the expression of P‐gp is up‐regulated in both GEM and DDP monodrug‐resistant cell lines, which indicated that P‐gp may play an important role in the combined effect of GEM and DDP, and our follow‐up research will in‐depth explore its function and mechanism in the synergism between GEM and DDP.…”
Section: Discussionmentioning
confidence: 58%
“…ABCB1 (also known as MDR1/multidrug‐resistance 1, P‐gp/P‐glycoprotein) is a plasma membrane protein and first discovered in multidrug‐resistant tumor cells. ABCB1 can extrude a large number of medically relevant compounds from cells and causes drug resistance 50–52 . In this study, we found that the expression of P‐gp is regulated by GEM or DDP or both, and also found that the expression of P‐gp is up‐regulated in both GEM and DDP monodrug‐resistant cell lines, which indicated that P‐gp may play an important role in the combined effect of GEM and DDP, and our follow‐up research will in‐depth explore its function and mechanism in the synergism between GEM and DDP.…”
Section: Discussionmentioning
confidence: 58%
“…It is located on the interface of the blood-brain barrier (efflux capacity of the protein protects the central nervous system from compounds with endogenous toxicity), placenta, liver, kidneys, colon and small intestine [ 161 , 162 , 163 , 164 , 165 , 166 , 167 ]. The transporter is involved in decreasing the oral bioavailability, tissue distribution and effectiveness of many therapeutic agents [ 168 ]. ABCG2 transporters are known to be responsible for limited exposure of the brain to anticancer drugs, the effectiveness of which reduces it, especially in case of brain metastases [ 169 ].…”
Section: Flavonoidsmentioning
confidence: 99%
“…The intracellular ensartinib was extracted and semi-quantified according to the methods reported in our previous studies [39,43]. Briefly, 2 × 10 6 cells were incubated with 10 µM ensartinib in the absence or presence of 10 µM tariquidar at 37 • C for 60 min and processed as described previously [39,43]. Mobile phase A: 0.1% formic acid in water.…”
Section: Ultra-performance Liquid Chromatography (Uplc)-selected Reac...mentioning
confidence: 99%
“…Knowing that P-gp expression confers resistance to ensartinib, and that one of the most likely explanations for this is the reduced intracellular drug accumulation caused by P-gp-mediated drug efflux [10], we examined the effect of P-gp function on the intracellular accumulation of ensartinib in cancer cells. KB-3-1 and the P-gp-overexpressing variant KB-V1 were treated with 10 µM ensartinib in the absence or presence of 10 µM tariquidar, and the intracellular concentration of ensartinib was determined using a liquid chromatographyselected reaction monitoring mass spectrometry (LC-SRM/MS) method (Figure 3a) as described previously [39,41,43]. Human KB epidermal cancer cell lines were chosen for this study since KB-V1 showed the highest RF value among all the P-gp-overexpressing cell lines (Table 1).…”
Section: P-gp Reduces the Intracellular Accumulation Of Ensartinib In...mentioning
confidence: 99%